(untitled) (Revista Lusófona de Educação, 2025)
This article examines how the creation of comics by newly arrived migrant and refugee youth can foster language learning, identity construction, and critical citizenship education. Based on the Comixx mit Klasse project, implemented in Hamburg schools since 2019, this qualitative- -exploratory study analyses 26 comics produced by students between 2019 and 2024. The results show that these multimodal texts portray migration trajectories, school experiences, aspirations, and emotional expressions, enabling learners to explore their expressive autonomy within a new sociocultural context. Through visual narratives, students articulate belonging, diversity, and social justice, challenging monolingual educational models and valuing plural linguistic repertoires. The study advocates for the use of comics as a transformative pedagogical resource, promoting more inclusive, participatory, and learner-centred learning environments, with strong potential to foster active citizenship and intercultural competence.